Perubahan Bentuk Tradisi Belis Dalam Adat Perkawinan Masyarakat Desa Golowatu Kabupaten Manggarai - Septiani, Maria Yosefina; Tamim, Imron Hadi; Pramestisari, Nyoman Ayu Sukma (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research examines the transformation of the belis tradition within the Golowatu Village community. The study aims to explore the changes in the form of the belis tradition, its cultural significance, and how it is practiced by the community. A descriptive qualitative method was employed for this research. The data analysis process involved collecting, reducing, and presenting data, followed by drawing conclusions. The informants for this study included couples who had participated in the belis tradition, traditional leaders, their families, and the surrounding community. The research was conducted in Golowatu Village. The findings reveal that the form of the belis tradition in the Golowatu Village community has indeed evolved, with a shift towards paying belis with money rather than animals, due to a significant decline in the animal population in the village. The cultural significance of belis in the Golowatu Village includes: 1) honoring a woman, 2) demonstrating the commitment and sacrifice of a man who wishes to marry her, and 3) expressing gratitude to the woman's parents for raising and nurturing her into adulthood. The traditional marriage practices in the Golowatu Village community also include two forms: shell marriage and hearth marriage. The types of belis that are offered in the belis tradition are animals and money. In the belis tradition, there are several stages of traditional marriage that use the belis system, namely initial introduction (hena one nai), family meeting (cumang ata tua), pongo, wagal, podo and wedi ruha.